The lived experiences of adults with attention-deficit/hyperactivity disorder: A rapid review of qualitative evidence - Ginapp, Callie M.; Macdonald-Gagnon, Grace; Angarita, Gustavo A.; Bold, Krysten W.; Potenza, Marc N. (Frontiers in Psychiatry, 2022)
Attention-deficit/hyperactivity disorder (ADHD) is a common condition that frequently persists into adulthood, although research and diagnostic criteria are focused on how the condition presents in children. We aimed to review qualitative research on lived experiences of adults with ADHD to characterize potential ADHD symptomatology in adulthood and provide perspectives on how needs might be better met. We searched three databases for qualitative studies on ADHD. Studies (n=35) in English that included data on the lived experiences of adults with ADHD were included. These studies covered experiences of receiving a diagnosis as an adult, symptomatology of adult ADHD, skills used to adapt to these symptoms, relationships between ADHD and substance use, patients’ self-perceptions, and participants’ experiences interacting with society. Many of the ADHD symptoms reported in these studies had overlap with other psychiatric conditions and may contribute to misdiagnosis and delays in diagnosis. Understanding symptomatology of ADHD in adults may inform future diagnostic criteria and guide interventions to improve quality of life.